دور فرسان مالطة وفرسان القديس ستيفان في القرصنة المتوسطية خلال العصر الحديث - بن معيزةمحمد شرعي; بوسليم,صالح (University of Eloued جامعة الوادي, 2024)
يتناول هذه المقال بالدراسة دور تنظيمات الفرسان في نشاط القرصنة البحرية في البحر الأبيض المتوسط خلال العصر الحديث، حيث برز في هذه الفترة تنظمان هامان، كان لهما حضور نشط في هذا المجال، ويتعلق الأمر بتنظيم فرسان مالطة، وتنظيم فرسان القديس ستيفان. وقد ارتبط ظهور هذين التنظيمين في بداية الأمر بالصراع العسكري خلال القرن العاشر الهجري/السادس عشر الميلادي، بين القوى الإسلامية وفي مقدمتها الدول العثمانية وإيالاتها بشرق المتوسط وغربه من ناحية، والقوى المسيحية بزعامة الإمبراطورية الإسبانية وحلفائها، خاصة من تنظيمات الفارسية، والنيابات السياسية بشبه الجزيرة الإيطالية...الخ، من ناحية أخرى. وإذا كانت هذه التنظيمات قد مثلت ذراعا عسكريا ضمن التحالف العسكري المسيحي خلال هذا القرن، فإنها لعبت بعد ذلك، خاصة خلال القرن السابع عشر الميلادي/الحادي عشر الهجري، دورا وظيفيا نيابة عن قوى التحالف، من خلال القيام بعمليات قرصنة بحرية ضد البحرية ، والسواحل الإسلامية. وقد كان لهذه العمليات تداعيات على بحرية وسواحل الحواضر الإسلامية بالبحر المتوسط، من خلال تهديد أمن الرعايا المسلمين، خاصة من التجار والحجاج، والاستيلاء على مختلف ممتلكاتهم المادية والمالية، مما فتح باب الصراع البحري بالمتوسط.This article examines the role of cavalry organizations in maritime piracy activity in the Mediterranean during the modern era, as two important organizations emerged during this period and had an active presence in this field. These are related to the organization of the Knights of Malta and the organization of Saint Stephen. The emergence of these two organizations was initially linked to the military conflict during the tenth century AH/ sixteenth century AD, between the Islamic powers, led by the Ottoman states and their provinces in the eastern and western Mediterranean on the one hand, and the Christian forces led by the Spanish Empire and its allies, especially the Persian organizations and the political procuratorates in the Italian peninsula. ...etc., on the other hand. If these organizations represented a military arm within the Christian military alliance during this century, they later played, especially during the seventeenth century AD/eleventh century AH, a functional role on behalf of the coalition forces, by carrying out maritime piracy operations against the navy and Islamic coasts. These operations had repercussions on the navy and coasts of Islamic cities in the Mediterranean, by threatening the security of Muslim nationals, especially merchants and pilgrims, and seizing their various material and financial properties, which opened the door to maritime conflict in the Mediterranean
Keywords: تنظيمات الفرسان; القرصنة; الغنائم البحرية; maritime piracy; cavalry organizations; naval spoils; prisoners